Kinetic resolution of sec-alcohols using a new class of readily assembled (S)-proline-derived 4-(pyrrolidino)-pyridine analogues - CONNON, STEPHEN (My University, 2005)
We report the development of a new class of readily prepared chiral 4-(pyrrolidino)-pyridine catalysts capable of exploiting both van der Waals (?) and H-bonding interactions, thus allowing remote chiral information to stereochemically control the kinetic resolution of sec-alcohols.
PUBLISHED
Keywords: Biochemistry; chiral catalyst